Chrysanthemum indicum extract inhibits NLRP3 and AIM2 inflammasome activation via regulating ASC phosphorylation. (15th July 2019) - Yu, Sang-Hyeun; Sun, Xiao; Kim, Myong-Ki; Akther, Mahbuba; Han, Jun-Hyuk; Kim, Tae-Yeon; Jiang, Jun; Kang, Tae-Bong; Lee, Kwang-Ho
Abstract: Ethnopharmacological relevance: Chrysanthemum indicum ( C. indicum ), a perennial plant, has long been used to treat inflammation-related disorders, such as pneumonia, hypertension, gastritis, and gastroenteritis. Aim of the study: The inhibitory effect of C. indicum extract (C.I) on inflammasome activation was investigated to validate its potential in treating inflammation related disorders. Materials and methods: LPS-primed bone marrow-derived macrophages (BMDMs) were used to confirm the inhibitory effect of C.I on selective inflammasome activation in vitro. A monosodium urate (MSU)-induced murine peritonitis model was employed to study the effect of C.I in vivo . Results: C.I inhibited activation of NLRP3 and AIM2 inflammasomes, leading to suppression of interleukin-1β secretion in vitro. Further, C.I regulates the phosphorylation of apoptosis-associated speck-like protein containing a CARD (ASC), which could be the main contribution to attenuate these inflammasomes activation. C.I also suppressed secretion of pro-inflammatory cytokines and neutrophils recruitment in MSU-induced murine peritonitis model. Conclusions: This study provides scientific evidence substantiating the traditional use of C. indicum in the treatment of inflammatory diseases, including gout, which is induced by physiologically analogous cause to MSU-induced peritonitis. Graphical abstract: Image 1